Space Technology to Monitor the Tornado That Hit Brahmanbaria Dist. of Bangladesh in 2013 and Damaged A Lot - Begum, Suraiya; Nessa, Mehrun; Alam, Md Shah; Ali, Md Saheb (Journal of Future Internet, 2014)
Bangladesh faces meteorological events like cyclone, depression , nor’easter’s, tornado etc. almost every year. Nor’wester’s and Tornadoes are the special type of storm which cause lot of destructions and hampers the sustainable development of the country. Nor’westers come mainly from the north westerly direction (and hence the name) and are land based. They are very common phenomenon in Bangladesh during late month of Chaitra and Baishak . They are known as Kalbaishaki in Bengali. The physical cause of such disasters is embodied in law of science and hence proper scientific research is necessary to deal with them. A massive tornado attacked Brahmanbaria dist. in 2013. In this paper , the role of Remote Sensing and GIS technology for monitoring the tornado and its impact have been described.